MEMAYU HAYUNING BAWANA DALAM PERSPEKTIF EKOANTROPOLOGI SASTRA - Suwardi Endraswara (HISKI, 2017)
The memayu hayuning bawana in Javanese society is much inspired by the poetic expression of a dalang and a poet. At the time the dalang performs seclusion and janturan, often revealing that context. Recognized or not, this phrase is one of the Javanese philosophy of life. The phrase has a sacred power that became the philosophy of believers. Memayu hayuning bawana revealed through literary texts, can be interpreted using the perspective of literary eco-anthropology. In the perspective of literary eco-anthropology, memayu hayuning bawana is a philosophical idea of the Javanese, to achieve peace of life. Not a bit of traditional or classical Javanese poetry that contains the concept of bayu hayuning bawana. This concept is an attempt by the Javanese to maintain the harmony, welfare, and peace of human life with the universe. In the pantun and tembang dolanan Jawa also contains the context of memayu hayuning bawana. The essence of the philosophy of life to lure hayuning bawana is to civilize the green culture in the universe. The green culture revealed through Javanese poetry is meant to preserve the universe. Pengayu hayuning bawana is an effort to reach the peak of life serenity. Even this phrase becomes a provision to reach manunggaling kawula-Gusti, when humans go to sangkan paraning dumadi.